HUBUNGAN ANTARA LITERASI SAINS DENGAN SIKAP ILMIAH SISWA SEKOLAH DASAR KELAS V DI GUGUS KALASAN - Putri Nur Azahro; Nurratri Kurnia Sari (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the relationship between science literacy and scientific attitudes among fifth-grade elementary school students in the Kalasan Cluster, Bendosari Subdistrict, Sukoharjo Regency. The low level of students’ science literacy, as indicated by the results of preliminary observations, served as the rationale for conducting this study. A quantitative correlational approach was used, employing a cluster random sampling technique. The research sample consisted of 24 students from two schools. Data were collected through multiple-choice tests and Likert-scale questionnaires. The instruments were tested for validity and reliability, yielding a Cronbach’s Alpha value of 0.898. A normality test using the Shapiro-Wilk test indicated that both variables were normally distributed. Hypothesis testing was conducted using the Pearson Product-Moment correlation technique with the assistance of IBM SPSS Statistics 25. The results showed a correlation coefficient of 0.940 with a significance level of 0.000 (p < 0.05), indicating a positive and very strong relationship between students’ science literacy and scientific attitudes. The higher the students’ level of science literacy, the better their scientific attitudes; this finding confirms that science literacy and scientific attitudes need to be developed simultaneously through active, contextual, and student-centered learning. ABSTRAK Penelitian ini bertujuan untuk mengetahui hubungan antara literasi sains dengan sikap ilmiah siswa kelas V SD di Gugus Kalasan, Kecamatan Bendosari, Kabupaten Sukoharjo. Rendahnya kemampuan literasi sains siswa yang ditunjukkan melalui hasil observasi awal menjadi latar belakang dilaksanakannya penelitian ini. Pendekatan yang digunakan adalah kuantitatif korelasional dengan teknik cluster random sampling. Sampel penelitian berjumlah 24 siswa yang berasal dari dua sekolah. Data dikumpulkan melalui tes pilihan ganda dan angket skala Likert. Instrumen telah diuji validitas dan reliabilitasnya dengan nilai Cronbach's Alpha sebesar 0,898. Uji normalitas menggunakan Shapiro-Wilk menunjukkan kedua variabel berdistribusi normal. Pengujian hipotesis dilakukan menggunakan teknik korelasi Pearson Product-Moment dengan bantuan IBM SPSS Statistics 25. Hasil penelitian menunjukkan koefisien korelasi sebesar 0,940 dengan nilai signifikansi 0,000 (p < 0,05), yang berarti terdapat hubungan positif dan sangat kuat antara literasi sains dan sikap ilmiah siswa. Semakin tinggi tingkat literasi sains siswa, semakin baik pula sikap ilmiahnya, temuan ini menegaskan bahwa literasi sains dan sikap ilmiah perlu dikembangkan secara bersamaan melalui pembelajaran yang aktif, kontekstual, dan berpusat pada siswa.